TUBE CHARGE WITH PROFILED SURFACE (Advances in Military Technology, 2022)
The paper describes the properties of the solid propellant tube charge being profiled on the outer surface and introduces the procedure of the main geometric characteristics determination. It is mainly aimed at the course of the burning surface variation of this type of the solid propellant charge in individual phases of burning.